Long‐term outcomes in pulmonary arterial hypertension by functional class: a meta‐analysis of randomized controlled trials and observational registries. (1st November 2020) - Kim, Nick H.; Fisher, Micah; Poch, David; Zhao, Carol; Shah, Mehul; Bartolome, Sonja
Abstract : Limited data about the long‐term prognosis and response to therapy in pulmonary arterial hypertension patients with World Health Organization functional class I/II symptoms are available. PubMed and Embase were searched for publications of observational registries and randomized, controlled trials in pulmonary arterial hypertension patients published between January 2001 and January 2018. Eligible registries enrolled pulmonary arterial hypertension patients ≥18 years, N  > 30, and reported survival by functional class. Randomized, controlled trial inclusion criteria were pulmonary arterial hypertension patients ≥18 years, ≥6 months of treatment, and morbidity, mortality, or time to worsening as end points reported by functional class. The primary outcomes were survival for registries and clinical event rates for randomized, controlled trials. Separate random effects models were calculated for registries and randomized, controlled trials. Four randomized, controlled trials ( n  = 2482) and 10 registries ( n  = 6580) were included. Registries enrolled 9%–47% functional class I/II patients (the vast majority being functional class II) with various pulmonary arterial hypertension etiologies. Survival rates for functional class I/II patients at one, two, and three years were 93% (95% confidence interval (CI): 91%–95%), 86% (95% CI: 82%–89%), and 78% (95% CI: 73%–83%), respectively. The hazard ratio for the treatment effect in randomized, controlled trials overall was 0.61 (95% CI: 0.51–0.74) and 0.60 (95% CI: 0.44–0.82) for functional class I/II patients and 0.62 (95% CI: 0.49–0.78) for functional class III/IV. The calculated risk of death of 22% within three years for functional class I/II patients underlines the need for careful assessment and optimal treatment of patients with functional class I/II disease. The randomized, controlled trial analysis demonstrates that current medical therapies have a beneficial treatment effect in this population.